Diagnostic Utility and Pitfalls of Tzanck Smear Cytology in Diagnosis of Various Cutaneous Lesions - Panwar, Hemlata (J Cytol, 2017)
AIMS: Tzanck smear is an old but useful test for diagnosis of cutaneous dermatoses. The aim of this study was to highlight the potential usefulness and diagnostic pitfalls of Tzanck smear for diagnosis of cutaneous dermatoses and infections. MATERIALS AND METHODS: This hospital based cross-sectional study was carried out on all Tzanck smears received for a period of twenty months (January 2014–August 2015). The smears were assessed to establish the utility of Tzanck smears in corroborating or excluding a diagnosis of immunobullous lesion or herpetic infection. Cases with discrepant diagnosis on histopathology were reviewed to identify additional cytomorphological features. RESULTS: A total of 57 Tzanck smears were performed during the study period. Out of the 18 clinically suspected cases of immunobullous disorders, Tzanck smear findings corroborated the clinical diagnosis in 7/18 cases, one case was diagnosed as cutaneous candidiasis, and diagnosis of immunobullous lesions could be excluded in 5/18 cases. Out of the 19 suspected cases of herpetic infections, viral cytopathic effect was observed in 8/19 cases. Besides immunobullous lesions and herpetic infections, acantholytic cells were also observed in spongiotic dermatitis and genodermatosis. Dyskeratotic keratinocytes seen in vacuolar interface dermatitis were not easily distinguishable from acantholytic cells on Tzanck smear. CONCLUSIONS: Tzanck smear test is an inexpensive and useful diagnostic tool for certain skin diseases. It can aid in establishing a rapid clinical diagnosis and can serve as a useful adjunct to routine histological examination. We recommend the use of Tzanck smear as a first-line investigation for vesiculobullous, erosive, and pustular lesions.